Fabrication And Characterization Of Thin Film On Polyethylene Terephthalate Substrate For Cigs Solar Cell - Faraj, Mohammad Ghaffar (2012)
The cost of the electrical energy generated by the solar cells was higher than that generated by fossil fuels. Cost reduction of the solar cell is therefore required. Feasibility of fabricating thin film CIGS solar cells on low-cost polyethylene terephthalate (PET) substrates in order to bring down the costs of the CIGS solar cell technology was explored.